A model for analysis, systemic planning and strategic synthesis for health science teaching in the Democratic Republic of the Congo: a vision for action - Levêque Alain; Coppieters Yves; Garant Michèle; Bapitani Josué; Kahombo Gérard; Parent Florence; Piette Danielle (BMC, 2004)
Abstract Background The problem of training human resources in health is a real concern in public health in Central Africa. What can be changed in order to train more competent health professionals? This is of utmost importance in primary health care. Methods Taking into account the level of training of secondary-level nurses in the Democratic Republic of the Congo (DRC), a systemic approach, based on the PRECEDE PROCEED model of analysis, led to a better understanding of the educational determinants and of the factors favourable to a better match between training in health sciences and the expected competences of the health professionals. This article must be read on two complementary levels: one reading, focused on the methodological process, should allow our findings to be transferred to other problems (adaptation of a health promotion model to the educational sphere). The other reading, revolving around the specific theme and results, should provide a frame of reference and specific avenues for action to improve human resources in the health field (using the results of its application in health science teaching in the DRC). Results The results show that it is important to start this training with a global and integrated approach shared by all the actors. The strategies of action entail the need for an approach taking into account all the aspects, i.e. sociological, educational, medical and public health. Conclusions The analysis of the results shows that one cannot bring any change without integrated strategies of action and a multidisciplinary approach that includes all the complex determinants of health behaviour, and to do it within the organization of local structures and institutions in the ministry of health in the DRC.